BOBOT PENGARUH MEROKOK TERHADAP KADAR TRIGLISERIDA PADA PASIEN SKIZOFRENIA YANG DIRAWAT INAP DI RSJ PROF SOEROYO MAGELANG - , Widea Rossi Desvita ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Schizophrenia is one of the most difficult mental disorders to treat and case severe damages. The most frequent comorbidities found in schizophrenia are smoking and metabolic syndrome, particularly hyperlipidemia. Nicotine in cigarettes possess âantipsychoticâ effect that can reduce the psychotic symptoms, but smoking is also associated with poor quality of life, the occurrence of metabolic syndrome, and higher mortality rate in schizophrenia. Hyperlipidemia in schizophrenia is mostly due to the use of antipsychotic, especially second generation antipsychotic, and smoking has the potential to worsen it. This study aimed to assess the effect of smoking on the occurrence of hyperlipidemia in schizophrenic patients. This study is a quantitative study with a cross sectional design. The study subjects are 120 schizophrenic patients from RSJ Prof. Dr. Soeroyo Magelang. The data collection will be done in January 2014 with the study instruments consist of sociodemographic instrument, questionnaire for smoking habits, and laboratorium examination for lipid status. Our results showed that the number of cigarettes smoked everyday was associated with the increase of triglyceride levels in schizophrenic patient. Bivariate and multivariate analyses showed that schizophrenic patients who smoke more than 20 cigarettes per day have higher risk of developing hypertriglyceridemia. Our study showed that smoking is a risk factor for lipid profile disorders in schizophrenia. The limitation of this study is that we cannot determine causative correlation between smoking and hypertriglyceridemiadue to the cross sectional design employed in our study. Our study only examineschizophrenicpatients who smoke and didnot use any control group as comparison. We also did not analyze the impact of antipsychotic treatment asconfounding factor in this study